Secondary School Students Learning From Reflections on the Rationale Behind Self-Made Errors: A Field Experiment. Issue 1 (2nd January 2016) - Heemsoth, Tim; Heinze, Aiso
Abstract : Thus far, it is unclear how students can learn most effectively from their own errors. In this study, reflections on the rationale behind self-made errors are assumed to enhance knowledge acquisition. In a field experiment with pre/post/follow-up design, the authors practiced fractions with 174 seventh- and eighth-grade students who were randomly assigned to one of two conditions: The students reflected on either the rationale behind their own errors or on the correct solution corresponding to their own errors. Students in the first condition group demonstrated a greater procedural knowledge at the posttest and at the follow-up test. Furthermore, at the follow-up test, these students demonstrated a higher conceptual knowledge. The implications for theory and school instruction are discussed.